Chemical analysis of H2–B2H6 and H2–CH4–B2H6 microwave CVD plasmas used for diamond deposition. (26th February 2016) - Rond, Catherine; Salem, Rania; Hamann, Stephan; Lombardi, Guillaume; Röpcke, Jürgen; Gicquel, Alix
Abstract: This study provides a detailed analysis of the H2 /B2 H6 chemistry and a first evaluation of H2 /CH4 /B2 H6 plasmas for conditions close to boron doped diamond microwave plasma assisted chemical vapor deposition. A H2 /B2 H6 chemical scheme composed of 38 reactions has been formulated from the research literature and finalized by an equilibrium approach of the gas composition. 1D thermochemical modeling of the gas phase provides a spatial description of the temperatures and of the mole fractions of the species. A comparison with the mole fractions of atomic boron and diborane measured by optical emission spectroscopy and tunable diode laser absorption spectroscopy in the mid-infrared region, respectively, have been performed on a wide range of operating conditions, i.e. for pressure values of p = 60–300 mbar, power values of P = 0.6–4 kW, diborane admixtures of 30 and 66 ppm and methane admixtures of up to 5% diluted in H2 . For the H2 /B2 H6 plasmas, the agreement between the experiments and the 1D model is satisfactory, especially for high power density conditions. At low power density, the electron processes would appear to be necessary to describe the diborane dissociation. Finally, the effect of methane addition to the H2 /B2 H6 mixture on the mole fraction of the atomic boron was investigated. At high pressure/power conditions, no significant influence was observed, whereas at low power densities the measured boron atom mole fractions decreased when methane was added.